2009
DOI: 10.1111/j.1742-4658.2009.07239.x
|View full text |Cite
|
Sign up to set email alerts
|

Bax distribution into mitochondrial detergent‐resistant microdomains is related to ceramide and cholesterol content in postischemic hearts

Abstract: Diverse changes have been described in mitochondria of apoptotic cells: the phospholipid content is modified, ceramide and GD3 concentrations increase, the cristae structure is modified, and nonresident proteins are recruited into the mitochondrial membranes. In particular, Bax, a Bcl‐2 family member protein, moves from the cytosol to the mitochondria, inducing cytochrome c release. Modifications of the content and distribution of specific lipids in the mitochondrial membranes, along with the well‐known partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Moreover, accumulation of endogenous ceramide by targeting bacterial SMase to mitochondria caused Bax translocation to mitochondria, cytochrome c release, and cell death (40,41). More recently, studies have reported that Bax preferentially associates with mitochondrial membrane microenvironments enriched in ceramide (26) and have also indicated that ceramide increases the membrane permeability of isolated mitochondria for cytochrome c release (42). Moreover, ceramide can form channels in mitochondrial outer membranes within the concentration range that is present in mitochondria during the induction phase of apoptosis (43), and additional studies showed that both recombinant human Bcl-x(L) and a C. elegans Bcl-2 homologue can disassemble ceramide channels in the mitochondrial outer membranes of isolated mitochondria from rat liver and yeast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, accumulation of endogenous ceramide by targeting bacterial SMase to mitochondria caused Bax translocation to mitochondria, cytochrome c release, and cell death (40,41). More recently, studies have reported that Bax preferentially associates with mitochondrial membrane microenvironments enriched in ceramide (26) and have also indicated that ceramide increases the membrane permeability of isolated mitochondria for cytochrome c release (42). Moreover, ceramide can form channels in mitochondrial outer membranes within the concentration range that is present in mitochondria during the induction phase of apoptosis (43), and additional studies showed that both recombinant human Bcl-x(L) and a C. elegans Bcl-2 homologue can disassemble ceramide channels in the mitochondrial outer membranes of isolated mitochondria from rat liver and yeast.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide has also been implicated in mitochondria-mediated apoptosis (22)(23)(24). However, the direct regulation of sphingolipids in mitochondria or mitochondria-associated membranes is mostly unclear with few reports detecting changes in mitochondrial ceramide in response to induction of apoptosis (25,26). This lack of information on SMase and other sphingolipid-regulating enzymes in mitochondria has significantly handicapped efforts to delineate signaling pathways in this organelle that involve sphingolipids.…”
mentioning
confidence: 99%
“…Furthermore, ceramide and activated Bax directly interact in vitro to synergistically induce outer membrane permeabilization in isolated mitochondria ( 61 ). Moreover, Bax association with ceramideenriched detergent-resistant membrane domains occurs in situ upon ischemia/reperfusion, a well-characterized apoptotic model ( 62 ). Further investigation has characterized the assembly of mitochondrial ceramide-rich macrodomains (MCRM) with enhanced association of Bax oligomers upon exposure to radiation ( 63 ).…”
Section: Ceramidementioning
confidence: 99%
“…The homogenates were cleared at 1,500 Â g, and the mitochondria were spun down at 10,000 Â g. Cholesterol depletion in the mitochondrial membranes was achieved by treatment with Me-b-cyclodextrin (b-MCD) (SigmaAldrich) as previously described. 72 Cholesterol enrichment was achieved by incubating isolated mitochondria with a cholesterol-BSA complex as described in Martínez et al 73 For cytochrome c release assays, 30 mg of crude mitochondria was resuspended at 1 mg/mL in KCl buffer supplemented with succinate (5 mM) and EGTA (0.5 mM). Peptides were added to the samples at various concentrations, and incubations were carried out at 30 C under agitation (300 rpm).…”
Section: Mitochondrial Assaysmentioning
confidence: 99%